2020
DOI: 10.3390/su12093522
|View full text |Cite
|
Sign up to set email alerts
|

Teaching towards Design-Based Learning in Manufacturing Technology Course: Sino–Australia Joint Undergraduate Program

Abstract: The internationalized higher education in Engineering has made the sustainable future of Chinese regional universities prosper in the recent decade. The teaching practices of engineering courses pose many challenges in Sino–foreign joint undergraduate programs. The design-based learning (DBL) approach addresses students learning challenges in the joint undergraduate program facilitated by the Wuhan University of Science and Technology (WUST) in central China along with Deakin University (DU), Australia. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Many researchers also discussed the application of DBL in specific teaching situations. They studied the teaching effectiveness of the DBL approach (Jiang et al, 2020 ). They focused on students' learning experiences (Ai et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers also discussed the application of DBL in specific teaching situations. They studied the teaching effectiveness of the DBL approach (Jiang et al, 2020 ). They focused on students' learning experiences (Ai et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al ( 2020 ) showed that the application of DBL in engineering education could foster individual sustainability competency. Jiang et al ( 2020 ) used the DBL approach to address the learning challenges of a joint undergraduate course in China and abroad and achieved satisfactory teaching and learning outcomes. Ai et al ( 2020 ) demonstrated that project-based design learning (PODBL) could be effective in improving industrial design teaching, increasing student learning efficiency and enhancing the learning experience.…”
Section: Introductionmentioning
confidence: 99%
“…O uso de PBL no contexto do ensino superior mostra-se como uma estratégia desafiadora por exigir que os acadêmicos desenvolvam níveis mais profundos de compreensão e aquisição de novas habilidades que o ajudarão a lidar com os desafios do mundo do trabalho (GUT-GARTS, 2020;ZAMORA-POLO, 2020;JIANG et al, 2020). Além disso, a utilização dessa metodologia propicia resolver desafios do mundo real, aplicando o conhecimento adquirido durante sua formação profissional (PORTUGUEZ CASTRO, GÓMEZ ZERMEÑO, 2020;MORALES, GÀRCIA, 2018).…”
Section: Engagement En La Escuela: Conceptualización Y Evaluación Resumounclassified
“…In these frames they studied the way of learning (including cross-disciplinary perspectives) and types of collaboration with local communities (Wooltorton et al, 2011). Due to the SDG, regional universities paid attention to the entrepreneurial development (Bratucu et al, 2020), manufactural development in China (Jiang et al, 2020;Xia, Li & Yin, 2020;Ma et al, 2020). At the same time, sustainable development poses a challenge to the regional universities in Finland (Lattu & Cai, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%